DESAIN DIDAKTIS KONSEP LUAS PERMUKAAN DAN VOLUME PRISMA DALAM PEMBELAJARAN MATEMATIKA SMP - Siti Aisah, Lusi; Kusnandi; Yulianti, Kartika (Universitas Wiralodra, 2016)
The purpose of this study is to composing didactic design concept about surface area and volume of prismsbased on learning obstacle (learning difficulties) students when studying the concept.The research methods is qualitative methods with data collection techniques are observation, question and answer, and documentation. The initial step in this research is identifying learning obstacle with learning obstacle instrument to students in grade IX junior high school and grade X senior hign scool who has studied about that concept. After learning obstacle is identified, the didactic design then composed by adjusting the learning theories that are relevant and does not reduce mathematical abilities that can be developed. Didactic design which has been arrangedthen implemented in the students learning process on grade VIII SMP. Didactic design effectiveness was measured using a modified degree increase of the gain normalized Hake. Didactic design has show considerable effectiveness, with an effective medium category. Results of the implementation and effectiveness of the didactic design shows that the didactic design that has been composed can be used as one of the alternative designs in studying the concept of surface area and volume of prisms.